Asignación de biomasa floral y distribución de las flores en la inflorescencia de Bactris gasipaes (Arecales: Palmae) - Cordero S, Roberto A (Universidad de Costa Rica, 1993)
Inflorescences of Baclris gasipaes (a moooecioos neolropica1 pahn) present a strong prezigotic resource allocation toward masculinity on the inflorescence. Male reproductive effort (ERM. biomass) was 0.82 ± 0.11 g male flowers I g inflorescence. A high conelatioo between me total inflorescence biomass with female reproductive effort (ERF) (r= 0.76), indicates that plants wim bigger inflorescences allocate more resources to ¡he female functioos. The pistillate flowers are situated preferentially in me inner pans of rachillas. Early ideas about evolution of protoginy, resource allocation and plant sexual systems are supported by these data.